2020
DOI: 10.36555/sosiohumanitas.v21i2.1242
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perencanaan dan Aset Pajak Tangguhan Terhadap Manajemen Laba Pada Perusahaan Telekomunikasi dan Konstruksi Yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2017

Abstract: Laporan keuangan berfungsi untuk mengkomunikasikan data keuangan dengan aktivitas perusahaan kepada pihak-pihak yang berkepentingan. Pihak yang berkepentingan tidak hanya manajemen tetapi juga otorisasi pajak, perbedaan kepentingan dan informasi tersebut mengakibatkan manajemen untuk melakukan strategi dalam mengolah data akuntansi yang dihasilkan. Manajemen laba merupakan salah satu cara dalam melakukan strategi pengolahan data akuntansi, melalui perencanaan pajak dan asset pajak tangguhan dalam laporan keuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
0
5
0
12
Order By: Relevance
“…The kind of data that used inside this research is quantitative data. The data derived from this study of secondary data (Yahya & Wahyuningsih, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The kind of data that used inside this research is quantitative data. The data derived from this study of secondary data (Yahya & Wahyuningsih, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Deferred Tax Liability is the amount of income tax payable in future periods as a result of taxable temporary differences. From this definition what must be understood is the concept of "recovery in future periods" for Deferred Tax Liabilities (Yahya & Wahyuningsih, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[19], [4], and [5] state that deferred tax assets have a positive effect on earnings management. On the other hand, [25] and [1] state that deferred tax assets do not affect earnings management, while [26] found that deferred tax assets have a negative effect on earnings management. [27] and [5] prove that deferred tax expenses have a positive effect on earnings management, but [26], [1], and [19] proves that deferred tax expenses affect earnings management.…”
Section: Introductionmentioning
confidence: 99%